Heart regeneration in the Mexican cavefish - Stockdale, W; Lemieux, M; Killen, A; Zhao, J; Hu, Z; Riepsaame, J; Hamilton, N; Kudoh, T; Riley, P; Van Aerle, R; Yamamoto, Y; Mommersteeg, M (Elsevier, 2018)
Although Astyanax mexicanus surface fish regenerate their hearts after injury, their Pachón cavedwelling counterparts cannot and, instead, form a permanent fibrotic scar, similar to the human heart. Myocardial proliferation peaks at similar levels in both surface fish and Pachón 1 week after injury. However, in Pachón, this peak coincides with a strong scarring and immune response, and ultimately, cavefish cardiomyocytes fail to replace the scar. We identified lrrc10 to be upregulated in surface fish compared with Pachón after injury. Similar to cavefish, knockout of lrrc10 in zebrafish impairs heart regeneration without affecting wound cardiomyocyte proliferation. Furthermore, using quantitative trait locus (QTL) analysis, we have linked the degree of heart regeneration to three loci in the genome, identifying candidate genes fundamental to the difference between scarring and regeneration. Our study provides evidence that successful heart regeneration entails a delicate interplay between cardiomyocyte proliferation and scarring.